Perioperative immunotherapy in gastric cancer: walking a fine line between hope and caution - Cai, Xianlei; Xiao, Xia; Zhang, Congcong; Yu, Weiming (Frontiers in Immunology, 2025)
Perioperative immunotherapy has emerged as an important strategy in the management of resectable gastric and gastroesophageal junction adenocarcinoma. Phase II and III studies combining immune checkpoint inhibitors with chemotherapy have shown higher pathological response rates and improvements in event-free outcomes, particularly in molecularly selected groups such as HER2-positive and MSI-H or dMMR tumors. MSI-H and dMMR cancers show marked sensitivity to immune treatment, often achieving high rates of pathological complete response. Combinations that include HER2-directed therapy and immunotherapy have also produced encouraging antitumor activity. However, the results in broader, unselected populations remain variable, and reliable predictive markers such as PD-L1 are still lacking. While safety profiles are generally acceptable, some treatment regimens, especially those involving antiangiogenic agents or dual checkpoint blockade, call for careful perioperative evaluation. Importantly, despite improvements in pathological and early clinical outcomes, the impact on overall survival has been limited so far, and longer follow-up is needed to clarify the true survival benefit. Future progress will depend on better patient selection through integrated molecular and immune markers, more thoughtful sequencing of therapies, and the development of combination strategies that can enhance the durability of response. These findings highlight both the promise of perioperative immunotherapy and the need for continued efforts to achieve meaningful survival gains.